The challenge of HIV/AIDS for theological education in Africa: Towards an HIV/AIDS sensitive curriculum - Maluleke, Tinyiko S. (Missionalia: Southern African Journal of Mission Studies, 2001)
The HIV/AIDS pandemic constitutes a new kairos for the church in (Southern) Africa. The church should overcome its theological impotence in the face of AIDS and learn from African Theology how to develop a contextually relevant theology to meet this new kairos.
Free